Visible Light–Induced Degradation of Inverted Polymer:Nonfullerene Acceptor Solar Cells: Initiated by the Light Absorption of ZnO Layer. Issue 1 (6th December 2020) - Liu, Bowen; Han, Yunfei; Li, Zerui; Gu, Huimin; Yan, Lingpeng; Lin, Yi; Luo, Qun; Yang, Shangfeng; Ma, Chang-Qi
Abstract : Power conversion efficiencies (PCEs) of polymer solar cells (PSCs) have exceeded 18% in the last few years. Stability has therefore become the next most important issue before commercialization. Herein, the degradation behaviors of the inverted PM6:IT‐4F (PBDB‐T‐2F:3, 9‐bis(2‐methylene‐((3‐(1, 1‐dicyanomethylene)‐6, 7‐difluoro)‐indanone))‐5, 5, 11, 11‐tetrakis(4‐hexylphenyl)‐dithieno[2, 3‐ d :2′, 3′‐ d ′]‐ s ‐indaceno[1, 2‐ b :5, 6‐ b ′]dithiophene) solar cells with different ZnO layers are systematically investigated. The PCE decay rates of the cells and the photobleaching process of the IT‐4F containing organic films on ZnO surface are directly correlated with the light‐absorption ability of the ZnO layer in the visible light range, indicating that photochemical decomposition of IT‐4F is initiated by the light absorption of ZnO layer. By analyzing the products of the aged ZnO/IT‐4F films with matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry (MALDI‐TOF‐MS), it is confirmed that photochemical reactions at the IT‐4F/ZnO interface include de‐electron‐withdrawing units and dealkylation on the side‐phenyl ring. Hydroxyl radicals generated by the photo‐oxidation of dangling hydroxide by ZnO are confirmed by electron spin resonance (ESR) spectroscopy measurements, which is attributed as the main reason causing the decomposition of IT‐4F. Surface treatment of ZnO with hydroxide and/or hydroxyl radical scavenger is found to be able to improve the stability of the PSCs, which further supports the proposed degradation mechanism. Abstract : Photo‐oxidation of the dangling hydroxyl group on ZnO surface under visible light illumination leads to the formation of hydroxyl radicals, which decompose the acceptor molecule IT‐4F and consequently decrease PM6:IT‐4F solar cell performance.